Analysis of process parameters of wastewater treatment of edible oils production - Dyachok, Vasyl; Marakhovska, Anastasia (Видавництво Львівської політехніки, 2017)
Investigated the liquid extraction method for possibility to sewage treatment of oils production plants. The mixture of organic solvent (extractant) for selective removal of the main pollutants of wastewater was selected. The resulting equilibrium line and operating line process was obtained. Established transfer steps number. The mathematical model of liquid-extraction wastewater treatment was built. The solution of model allows to predict the kinetics of wastewater extraction for implementing the technology in practice. The equipment to design the flowsheet of liquid extraction method for wastewater treatment of food oils production was matched.
Keywords: liquid extraction; extractant; rafinate; extract; wastewater; mass transfer coefficient; mathematical model